Selected biomechanical and kinanthropometrical factors in relation to penalty corner performance in field hockey - Viswanat, S.; Kalidasan, R. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of the study was to find out the relationship between biomechanical, kinanthropometric and performance factors in penalty corner push- in. Male (n=20) university field hockey players were randomly selected from Chennai city colleges for this study, the age of the subjects ranged from 18 to 28 years. The high definition camera (DCR SR65) was used to record the performances that were approximately transverse to the trajectory of the ball of the push in. The subjects were made to take three trials only. The collected data by using video camera were analysed through the "Silicon Coach Pro 7" Software. Video footage was digitized for data analysis of ball speed, drag time, stance width, front knee angle, right elbow angle, rear knee angle. Kinanthropometric variable such as height, weight, arm length, arm span, palm length, palm span. The data was analyzed by use of Pearson`s product moment correlation using SPSS. The finding reveals that rear knee angle and height of the player showed significant relationship to the performance of penalty corner Push-in.